Investigating charge-up and fragmentation dynamics of oxygen molecules after interaction with strong X-ray free-electron laser pulses. Issue 44 (7th November 2022) - Kastirke, G.; Ota, F.; Rezvan, D. V.; Schöffler, M. S.; Weller, M.; Rist, J.; Boll, R.; Anders, N.; Baumann, T. M.; Eckart, S.; Erk, B.; De Fanis, A.; et al.
Abstract : The X-ray-induced charge-up and fragmentation process of a small molecule is examined in great detail by measuring the molecular-frame photoelectron interference pattern in conjunction with other observables in coincidence. Abstract : During the last decade, X-ray free-electron lasers (XFELs) have enabled the study of light–matter interaction under extreme conditions. Atoms which are subject to XFEL radiation are charged by a complex interplay of (several subsequent) photoionization events and electronic decay processes within a few femtoseconds. The interaction with molecules is even more intriguing, since intricate nuclear dynamics occur as the molecules start to dissociate during the charge-up process. Here, we demonstrate that by analyzing photoelectron angular emission distributions and kinetic energy release of charge states of ionic molecular fragments, we can obtain a detailed understanding of the charge-up and fragmentation dynamics. Our novel approach allows for gathering such information without the need of complex ab initio modeling. As an example, we provide a detailed view on the processes happening on a femtosecond time scale in oxygen molecules exposed to intense XFEL pulses.